MEMAKSIMALKAN PERAN ORANG TUA DALAM PEMBELAJARAN JARAK JAUH (STUDI ANALISIS MENGATASI KEJENUHAN BELAJAR PADA ANAK JENJANG PENDIDIKAN DASAR) - Alawiyah, Fakhriyatus Shofa (PSGA LP2M IAIN Pontianak, 2023)
The purpose of this article is to describe and analyze the maximal role of parents in distance learning related to the learning saturation of elementary school children at SDN Tanggul Wetan 2, of which the implementation is due to the emergency period of Corona Virus disease (Covid-19) which hit Indonesia today that has an impact on all learning activities in the school is diverted with distance learning from their homes. The writing of this article is based on a mini-research on maximizing the role of parents in overcoming the saturation of learning the basic child education level at SDN Tanggul Wetan 2, Jember. related to the implementation of distance learning. The study used a qualitative approach using the type of analysis study design. This study uses interview data collection techniques and document studies. Validity of data using credibility. Then analyzed critically by using theories about parental roles and children learning saturation. Results of the study: first, the role of parents in distance learning is as ' a substitute for school teachers ', facilitators and motivators. Second, the learning saturation factors in the child of SDN Tanggul Wetan 2: Lack of communication with peers, methods, places and a monotonous learning atmosphere, lack of activity outdoors, mental tension while learning. Third, to overcome child learning saturation during distance learning, parents maximize their role as: (1) Educators, ' teacher substitutes ', by: accompanying the children while studying, guiding and directing to prepare for learning activities, praying together before and after learning, evaluating children's assignments before being sent to school teachers, playing together, acting as peers, (2) facilitators by: Providing mobile phones, books, computer/laptop for parents who are financially able to, change the physical study room, invite children to study in another room, home porch, occasionally invite children to wear school uniforms while studying, providing Internet access, providing a television-based learning media (TVRI), (3) motivator, by the way: encouraging the tasks of the school, giving praise to the children after successfully working on the tasks of the school teacher, giving the award, invite the child to always pray that the disaster is soon passed and can study in the school as usual.